Peningkatan Pengetahuan dalam Pencegahan Penularan TB Paru pada Anak - Abimulyani, Yumi; Geddy, Nancy Vonny; Sulistiyowati, Anisa Nanang (Lembaga Pengembangan Kinerja Dosen, 2025)
Tuberculosis (TB) is the ninth leading cause of death worldwide, surpassing HIV/AIDS. In 2016, TB-related deaths among HIV-negative individuals reached 1.3 million, while deaths among those with HIV-TB co-infection totaled 374,000. Indonesia ranks among the top five countries with the highest TB burden, accounting for approximately 5.8% of global TB cases. The TB prevalence rate in Indonesia in 2016 was 391 per 100,000 population, with nearly half of the cases occurring among women of reproductive age. It is estimated that 1–3% of pregnant women have TB, and some are also co-infected with HIV. The national target for TB elimination by 2030 is to reduce incidence to 65 per 10,000 population and mortality to 6 per 100,000 population. However, in Mimika District, the TB incidence remains high at 707 per 10,000 population, with a mortality rate of 27 per 100,000 population.This community service program aimed to improve knowledge regarding the prevention of pulmonary TB transmission from adults to toddlers living in the same household, in order to break the chain of transmission. The activity was conducted from July to September 2024 in Kamoro Jaya Subdistrict, under the jurisdiction of Wania Health Center, with 90 participants consisting of mothers with toddlers and community health volunteers (Posyandu cadres).Methods used included lectures, group discussions, and demonstrations. The educational material focused on the prevention of TB transmission in children. Participants completed a questionnaire before the activity. The results showed an increase in knowledge regarding the prevention of pulmonary TB in children.